The Implementation of Quizizz Application in Teaching General English in Higher Education - Ratih Inayah (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study investigates the implementation of Quizizz, a game-based learning platform, in teaching General English to university students. The primary aim is to explore how such digital tools can enhance student engagement and motivation in higher education contexts. A qualitative descriptive research design was employed to gather in-depth insights from participants. The data were collected through classroom observations, student questionnaires, and interviews with both students and lecturers involved in the General English course. The participants included 32 students from a private university who actively used Quizizz during the learning process. The data were analyzed thematically to identify patterns and perceptions related to the use of the application. The findings indicate that the use of Quizizz significantly developed student engagement and motivation. Students reported feeling more motivated and interested when learning activities involved interactive quizzes. The real-time feedback, competitive features, and game-like format of Quizizz were found to enhance their focus and reinforce their understanding of vocabulary and grammar. In sum, the implementation of Quizizz in teaching General English offers practical benefits by creating a more dynamic and student-centered classroom environment. It also contributes to the growing body of research on technology-enhanced language learning in higher education.